2021
DOI: 10.1590/1806-9061-2020-1362
|View full text |Cite
|
Sign up to set email alerts
|

Phytobiotic Effect of Anacardium occidentale L. Leaves Powder on Performance, Carcass Traits, and Intestinal Characteristics in Broilers

Abstract: In order to evaluate the phytobiotic effect of cashew (Anacardium occidentale L.) leaves powder (CLP) on growth performance, carcass traits, lymphoid organ weights and cecal lactic-acid bacteria in broilers, a total of 720 unsexed broilers of the Ross 308® genetic line were distributed according to a completely randomized design with three experimental treatments, five repetitions and 48 chickens per repetitions. The experimental treatments consisted of a basal diet (DB; T0) and DB + supplementation with 0.50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Although G. lucidum powder did not change (p>0.05) broiler's growth performance (Table 5), this natural product did promote a higher carcass yield, perhaps due to better intestinal health, which allowed for the increase of muscle synthesis. Other authors Farag & El-Rayes (2016) and Martínez et al (2021b) reported similar results in carcass yields when they used small concentrations of natural alternatives rich in beneficial secondary metabolites (mainly tannic, coumarins, polysaccharides, flavonoids, and alkaloids). Azad et al (2013) and Mashayekhi et al (2018) have informed that the positive effects of these secondary metabolites on broiler carcass yields have been related to nutrient absorption, mainly that of essentials amino acids such as lysine, methionine, and threonine.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…Although G. lucidum powder did not change (p>0.05) broiler's growth performance (Table 5), this natural product did promote a higher carcass yield, perhaps due to better intestinal health, which allowed for the increase of muscle synthesis. Other authors Farag & El-Rayes (2016) and Martínez et al (2021b) reported similar results in carcass yields when they used small concentrations of natural alternatives rich in beneficial secondary metabolites (mainly tannic, coumarins, polysaccharides, flavonoids, and alkaloids). Azad et al (2013) and Mashayekhi et al (2018) have informed that the positive effects of these secondary metabolites on broiler carcass yields have been related to nutrient absorption, mainly that of essentials amino acids such as lysine, methionine, and threonine.…”
Section: Resultsmentioning
confidence: 61%
“…Therefore, the highest immunological activity in birds generally occurs with the involution of the primary lymphoid organs (Bursa de Fabricio and thymus). Moreover, Martínez et al (2021b) have reported the same effect on relative spleen weight when they used natural products rich in secondary metabolites (mainly tannins, coumarins, flavonoids, and with reduced sugars) in broilers. Other studies have found that the Ganoderma lucidum mushroom increases the spleen index in apparently healthy and sick laboratory animals (rats and mice), indicating a higher immune response (Wang et al, 2013;Zhu et al, 2019;Li et al, 2019;.…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…The chemical characterization of feeds is one of the most important aspects for the successful development of livestock production and complements the in vitro and in vivo results. Thus, these chemical studies are essential to formulate diets considering the animal species, productive category, physiological state, and productive purpose (Betancourt et al, 2017), which will allow taking advantage of the available raw materials and lowering the production costs associated with feeding (Martínez & Valdivié, 2021).…”
Section: Discussionmentioning
confidence: 99%